Design methodology of a low pressure turbine for waste heat recovery via electric turbocompounding. (25th August 2016) - Bin Mamat, Aman M.I.; Martinez-Botas, Ricardo F.; Rajoo, Srithar; Hao, Liu; Romagnoli, Alessandro
Highlights: A design methodology for a high-performance low-pressure turbine was presented. A meanline model was used in the preliminary design, followed by CFD optimization. The LPT operates at low pressure ratios, PR ≈ 1.05–1.3 with 0.758 efficiency. Experimental testing validates the performance of the LPT designed by this method. Test on an engine fitted with the LPT show a 2.6% maximum reduction of BSFC. Abstract: This paper presents a design methodology of a high performance Low Pressure Turbine (LPT) for turbocompounding applications to be used in a 1.0 L "cost-effective, ultra-efficient heavily downsized gasoline engine for a small and large segment passenger car". Under this assumption, the LPT was designed to recover the latent energy of discharged exhaust gases at low pressure ratios (1.05–1.3) and to drive a small electric generator with a maximum power output of 1.0 kW. The design speed was fixed at 50, 000 rpm with a pressure ratio, PR of 1.08. Commercially available turbines are not suitable for this purpose due to the very low efficiencies experienced when operating in these pressure ratio ranges. By fixing all the LPT requirements, the turbine loss model was combined with the geometrical model to calculate preliminary LPT geometry. The LPT features a mixed-flow turbine with a cone angle of 40° and 9 blades, with an inlet blade angle at radius mean square of +20°. The exit-to-inlet area ratio value is approximately 0.372 which is outside of the conventional range indicating the novelty of the approach. A single passage Computational Fluid Dynamics (CFD) model was applied to optimize the preliminary LPT design by changing the inlet absolute angle. The investigation found the optimal inlet absolute angle was 77°. Turbine off-design performance was then predicted from single passage CFD model. A rapid prototype of the LPT was manufactured and tested in Imperial College turbocharger testing facility under steady-state and pulsating flow. The steady-state testing was conducted over speed parameter ranges from 1206 rpm/K 0.5 to 1809 rpm/K 0.5 . The test results showed a typical flow capacity trend as a conventional radial turbine but the LPT had higher total-to-static efficiency, η t - s in the lower pressure ratio regions. A maximum total-to-static efficiency, η t - s of 0.758 at pressure ratio, PR ≈ 1.1 was found, no available turbines exist in this range as parameters. A validation of the predicted single passage CFD analysis for the off-design performance against the LPT test result found a minimum total-to-static efficiency Standard Deviation of ±0.026 points for the speed parameter of 1507 rpm/K 0.5 . A minimum Mass Flow Parameter Standard Deviation of ±0.091 kg/s K 0.5 bar is found at 1206 rpm/K 0.5 .